Manajemen Fitness Center Atlas Sport Club Surabaya - Dimas Altino Kasisyah; Nortje Anita Kumaat (STIKes Ibnu Sina Ajibarang, 2024)
This study aims to analyze management at Atlas Sport Club Surabaya, covering aspects of planning, organizing, directing, and controlling. The research employs a descriptive qualitative approach, using a survey focused on descriptive methods. The sampling technique used is snowball sampling, with subjects including HRD, the gym manager, fitness instructors, graphic designers, the head of marketing, and marketing communications. The instruments used include observation sheets, interviews, and documentation. Data analysis is conducted through steps of reduction and presentation to draw conclusions. The research findings indicate that: (1) Planning at the Fitness Center Atlas Sport Club Surabaya has been aligned with organizational goals. The plans include well-structured long-term and short-term work programs based on sports management principles. (2) The organizing aspect shows a harmonious working relationship between the manager, fitness instructors, and the front office, reflecting alignment with sports management practices. The organizational structure has been effectively coordinated, with the manager maintaining an open attitude and motivation to enhance the fitness center's well-being. Each employee performs tasks in accordance with the terms outlined in their contracts. Directing at the fitness center is effectively carried out through team formation that involves a personal approach to employees. (3) Employee direction can occur at any time by leaders, including the owner, manager, and HRD. Direction from the manager and HRD takes place daily via WhatsApp groups. (4) Supervision at the fitness center is conducted effectively. HRD and the team perform daily evaluations, while the manager conducts monthly evaluations alongside financial reports and target achievements.In conclusion, management at the Atlas Sport Club Fitness Center in Surabaya operates according to management functions. The study suggests that Atlas Sport Club should address infrastructure improvements for facilities that are beginning to deteriorate, and it is recommended that the fitness center add more equipment to support operations.